Atherogenic Dyslipidemia in Latin America: Prevalence, causes and treatment: Expert's position paper made by The Latin American Academy for the Study of Lipids (ALALIP) Endorsed by the Inter-American Society of Cardiology (IASC), the South American Society of Cardiology (SSC), the Pan-American College of Endothelium (PACE), and the International Atherosclerosis Society (IAS). (15th September 2017) - Ponte-Negretti, Carlos I.; Isea-Perez, Jesus E.; Lorenzatti, Alberto J.; Lopez-Jaramillo, Patricio; Wyss-Q, Fernando Stuardo; Pintó, Xavier; Lanas, Fernando; Medina, Josefina; Machado-H, Livia T.; Acevedo, Monica; Varleta, Paola; Bryce, Alfonso; et al.
Abstract: This is an executive summary made by a group of experts named Latin American Academy for the study of Lipids (ALALIP). In the current clinical guidelines, atherogenic dyslipidemia (AD) is a poorly recognized entity. Due to the frequent lipid alterations associated with AD in Latin America (LA), we organized a group of experts named (ALALIP) to generate a document in order to analyze their prevalence and to offer practical recommendations. Methodology: using the Delphi methodology, we conducted a comprehensive literature review with emphasis on those publications related to LA. Subsequently, we developed key questions for discussion. As a convention, those recommendations that had a 100% of acceptance were considered unanimous, those with >80% were consensual, and those with <80% were in disagreement. Results: a systematic analysis of national health surveys and regional cohort studies showed a consistently high prevalence of the lipid abnormalities that define AD: low levels of high-density lipoprotein cholesterol (HDL-C) range from 34.1% to 53.3% and elevated triglycerides (TG) range from 25.5% to 31.2%. These abnormalities could be related to high consumption of food with a high caloric density, cholesterol and trans fats, a sedentary lifestyle and perhaps epigenetic changes Conclusions: lipid abnormalities that define AD have a high prevalence in LA. The interaction between an unfavorable lifestyle, inheritance and epigenetic changes is probably their cause. It is important to design a global study of risk factors in LA to know its true prevalence in the region, its consequences and to derive from its treatment strategies.